PHARMACEUTICAL TERMINOLOGY IN LATIN - qizi, Hamroyeva Bonu Baxtiyor; Xamidovna, Xamdamova Muqaddas (Research Focus International Scientific Journal, 2026)
This article analyzes the fundamental role of Latin terminology in the modern pharmaceutical field and its importance in shaping international drug nomenclature. Although Latin is considered a “dead language” in the age of artificial intelligence and digital technologies in pharmacy it continues to play an important role as a lingua franca. The study considers the unification of the nomenclature of medicinal plants, dosage forms, and traditional Latin abbreviations in prescriptions. Statistical data and comparative analyses show that the correct use of Latin terminology helps reduce medication errors in pharmaceutical practice by up to 15–20%. In conclusion, Latin in pharmaceutical education and in the global healthcare system appears not only as a tradition, but also as a guarantee of safety and precision.